PARENTAL MENTORING APPROACH TO ADDRESS SOCIAL INTERACTION OF AUTISTIC CHILDREN FROM A COUNSELING PERSPECTIVE - Mustoha, Siti Sarah Binti (Jurnal Konseling Pendidikan Islam, 2025)
This research is entitled "Parental Assistance Approach to Overcoming Social Interactions of Autistic Children in a Counseling Perspective". Social interaction in autistic children is a social disorder in the form of difficulties in understanding and building social relationships with the people around them who require help from parents to overcome their social interaction problems. This research aims to determine the social interaction abilities of autistic children and determine the parental assistance approach in dealing with the social interactions of autistic children from a counseling perspective. This research uses qualitative methods with field types. The researcher's data collection techniques used interview techniques and documentation by subjects and data analysis techniques used pattern matching, time series, and data explanation. The results of this research show that the ability and approach of mentoring by parents to overcome the social interactions of autistic children as found from the results of interviews with the subject, Amir shows good development from the assistance of his parents. It can also be concluded that the approach used by parents to accompany the social interactions of autistic children helps Amir's development to recover well even though there are still some social interactions Amir still cannot master well.